The Effect of Economic Factors on Competitive Advantage of Consumer Goods Manufacturing Companies in Nigeria - Adedoyin Opeyemi Okusanya; T. A. Hassan; O. O. Adeniji; Adedoyin A. Obisanya (Mimbar Ilmu, 2025)
Consumer goods manufacturing industry owners and managers find it challenging and difficult in constantly and continuously achieving targeted business performance occasioned by their inability to achieve competitive advantage resulting from global economic activities. This study investigates the examining the effect of economic factors on competitive advantage of consumer goods manufacturing companies in Nigeria. The study adopted cross sectional survey research design. A sample size of 568 was used. The primary data was collected through administering copies of questionnaire to the target respondents. A self-developed structured and validated questionnaire was used for data collection. The reliability test yielded Cronbach’s alpha for the constructs ranging from 0.745 to 0.892. The response rate was 87.7%. Data were analyzed using inferential statistics (Multiple regression analysis). Findings revealed that The results revealed that interest rate (β = 0.126, t = 2.143, p = 0.033), importation policy (β = 0.288, t = 3.996, p = 0.000), infrastructural facility (β = 0.285, t = 4.065, p = 0.000) and exchange rate (β = 0.313, t = 4.357, p = 0.000) have positive and significant effects on competitive advantage of the selected quoted consumer goods companies in Nigeria. It was recommended that Managers or consumer goods owners should factor in economic policies on importation policy, inflation rate, infrastructural facility, interest rate and exchange rates so as to proactively determine the trend effect of economic policies on competitive advantage of selected quoted consumer goods companies in Nigeria.